Review of Oriental species of the genus Atopotrophos (Hymenoptera: Ichneumonidae) - Reshchikov, Alexey (Zootaxa, 2024)
A new species of tryphonine Darwin Wasps in the genus Atopotrophos Cushman, 1919, (A. bubeng sp. nov.). is described from Bubeng, Mueang La, Xishuangbanna, Yunnan Province. The new species can be distinguished from all other Atopotrophos species by having 35 flagellomeres, a very short malar space, both scutellum and postscutellum with apical teeth, and from the most similar species, A. spiniger, by its larger size, longer area superomedia, longer T1, and shorter ovipositor. Re-descriptions, illustrations of holotype specimens of A. chinensis and A. spiniger are provided. The type localities of these species are defined, and approximate coordinates and habitat description are added. A key for Oriental species is provided.